Use of ivermectin in patients with covid-19: a narrative review - Castañeda-Marín, Elio (2021)
Introduction. Towards the end of the last month of 2019, a new highly contagious coronavirus was identified in China causing the start of a new pandemic. Millions of infected people and thousands of deaths are the result of SARS-CoV-2 infection; different therapeutic strategies have been proposed for its treatment, one of them has been ivermectin, causing discrepancies in the medical community regarding its use. We set out to review the available scientific evidence on the use of ivermectin in the context of IDVC-19 in humans. A literature search was conducted on the following databases: Pub Med, Web of Science, Cochrane, Clinical Trials, and ISRCCTN using search expressions that include the following terms: ivermectin, antiviral, virus, covid-19 and/or SARS-CoV-2. There is no scientific evidence to support the use of ivermectin as a treatment and/or prophylaxis for SARS-CoV-2 infection.